Comparative assessment of low back pain and its determinants among Iranian male general dentists and pharmacists - Omid Aminian (Journal of Dental Medicine, 2013)
Background and Aims: Regarding the diversity of reported low- back pain among dentists in different countries and lack of control group in most of the previous studies, the purpose of this study was to compare low- back pain and related risk factors between male general dentists and pharmacists to determine the relation between dentistry and development of low back pain.   Materials and Methods: In this cross-sectional study, 261 male dentists were compared with 193 male pharmacists as a control group with Standardized Nordic Questionnaire (low back section). Subjects were at least one year in clinical practice after becoming qualified and did not suffer from connective tissue diseases and history of a traumatic event causing fracture in spinal column. The data were analyzed by Chi- square, T-test and logistic regression analyses.   Results: The prevalence of low back pain in the past 12 months was 54.8% in male dentists and 36.3% in male pharmacists (P=.001). Logistic regression analyses, adjustmenting for occupation, age, body mass index (BMI), smoking, working years and working hours per week, revealed that there was a significant association between being a dentist and having low- back pain (OR=2.54, P=0.001).   Conclusion: Dentistry as a profession in male gender is associated with low back pain, independent of age, body mass index (BMI), smoking, working years and working hours per week.